1986
DOI: 10.1038/319776a0
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of intracellular calcium reduces voltage-dependent potassium conductance in human T cells

Abstract: Both voltage-activated potassium channels and the concentration of free intracellular calcium have been implicated in the activation of T lymphocytes. Using the patch-clamp technique, we now show an unexpected relationship between the level of intracellular calcium [Ca]i in human lymphocytes and the amplitude of a voltage-dependent current: the elevation of [Ca]i decreases the potassium conductance. This is in contrast to other systems where [Ca]i activates K+ channels. Our results suggest that the level of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
2

Year Published

1987
1987
2001
2001

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(56 citation statements)
references
References 17 publications
6
48
2
Order By: Relevance
“…Dupuis et al (1989) have, in addition, found that in cells displaying a PHA-sensitive Ca2+ current, IK(V) was inhibited probably by an increase in internal Ca2+. Bregestovski, Redkozubov & Alexeev (1986) demonstrated that IK(V) is inhibited by intracellular Ca2+ and this relationship may account for the failure of other groups to detect any reproducible effect on IK(V) in human T-cells by PHA or phorbol esters (Deutsch, Krause & Lee, 1986;Schlichter, Sidell & Hagiwara, 1986b). Our patchclamp studies showed a low density of voltage-gated K+ channels in resting rat thymocytes and no activation of this class of K+ channels by ConA.…”
Section: Discussionmentioning
confidence: 78%
“…Dupuis et al (1989) have, in addition, found that in cells displaying a PHA-sensitive Ca2+ current, IK(V) was inhibited probably by an increase in internal Ca2+. Bregestovski, Redkozubov & Alexeev (1986) demonstrated that IK(V) is inhibited by intracellular Ca2+ and this relationship may account for the failure of other groups to detect any reproducible effect on IK(V) in human T-cells by PHA or phorbol esters (Deutsch, Krause & Lee, 1986;Schlichter, Sidell & Hagiwara, 1986b). Our patchclamp studies showed a low density of voltage-gated K+ channels in resting rat thymocytes and no activation of this class of K+ channels by ConA.…”
Section: Discussionmentioning
confidence: 78%
“…Current through voltage-gated K + channels can also be observed in many of the records as an upward deflection at more positive potentials. The ramp protocol with elevated [Ca2+]i reduces the size of voltage-gated currents, because the use-dependent inactivation exhibited by K(V) channels during repetitive depolarization is accentuated by calcium ions from the inside Bregestovski, Redkozubov, and Alexeev, 1986;Grissmer and Cahalan, 1989b).…”
Section: Activation Of K(ca) Channels During Whole-cell Recordingmentioning
confidence: 99%
“…Experimental methods, data recording on FM tape (Bruel & Kjaer, Denmark) and offline computer (Labtam, Australia) analysis procedures are similar to those previously described elsewhere in detail (Bregestovski et al, 1986;Takeda et al, 1987). Pipettes for whole cell recording had resistances of 3-7 MO.…”
Section: Electrophysiologymentioning
confidence: 99%